Strangulated internal hernia through the lesser omentum with intestinal necrosis: a case report - Duarte, Gustavo Gibin; Fontes, Belchor; Poggetti, Renato Sérgio; Loreto, Marcos Roberto; Motta, Paulo; Birolini, Dario (São Paulo Medical Journal, 2002)
CONTEXT: Internal hernias account for only 0.2 to 0.9% of the cases of intestinal obstruction. They do not have specific clinical manifestations, and are usually diagnosed during laparotomy for acute intestinal obstruction. Internal hernias through the lesser omentum are extremely rare. CASE REPORT: We report here the case of a 36-yearold patient who underwent exploratory laparotomy for acute intestinal obstruction. An internal hernia through the lesser omentum was found, with a strangulated ileal segment passing through the perforation into an abscess within the lesser sac. The surgical procedures included ileal resection, primary anastomosis, abscess removal, and placement of a drain in the lesser sac. The patient was reoperated 6 days later for abdominal sepsis; a lesser sac abscess was removed and the abdominal incision was left open. The patient stayed in the Intensive Care Unit for 15 days, and eventually left the hospital on the 28th post-admission day, with complete recovery thereafter. CONCLUSION: The early diagnosis of acute intestinal obstruction and immediate indication for laparotomy is the main task of the surgeon when faced with a case of acute abdomen with a hypothesis of internal hernia, so as to minimize severe postoperative complications, as illustrated by the present case.